Constructing Human Integrity in the Perspective of Sunda Wiwitan Religious Ethics - Alfonsus Sutarno; Bartolomeus Samho; Oscar Yasunari (State Institute of Islamic Studies (IAIN) Salatiga, 2023)
This paper examines human integrity from the perspective of localÂ religion of Sunda Wiwitan in Cigugur, Kuningan, West Java, Indonesia.Â We collected research dataÂ using qualitative research strategies throughÂ in-depth interviews, participantÂ observation, and literature research.Â The complexity of humanity is explored andÂ internalized by variousÂ groups, including indigenous peoples. Human integrity occurs whenÂ there is unity between the physical and spiritual aspects. The physicaland spiritual aspects of a healthy and harmonious human being are aÂ marker for humanity that is human (homo humanum) and even has aÂ divine dimension (homo religious). The core of the construction of humanÂ integrity in the Sunda Wiwitan Religious Ethics is when there is an attitudeÂ of â€œsilihâ€, or â€œsalingâ€, i.e, reciprocated acts of kindness toward each other.Â This attitude is further described as an attitude or behavior of makingÂ each other fragrant or silih wangi. This means that humans (must) protectÂ each otherâ€™s reputation and do well to others, and that they are motivatedÂ to eliminate each otherâ€™s weaknesses or shortcomings; humans show themutual behavior of silih asah (meaning that humans educate one another,Â are willing to share knowledge, understanding, and skills); humans showÂ a mutual caring behavior or silih asuh (humans protect one another, giveÂ to each other, help each other in need and distress); humans love oneÂ another or showing the behavior of silih asih. This local wisdom relatedÂ to Sunda Wiwitan humanism is increasingly relevant for todayâ€™s globalÂ society in reflecting on the meaning and essence of humanity.Â